Implementasi Strategi Pengelolaan Uang Kuliah Tunggal Pada Masa Pandemi Covid 19 Di Universitas Palangka Raya Dengan Pendekatan Analisis SWOT - Tahasak Tahasak; Yunikewaty Yunikewaty; Y Joni Pambelum (FKIP, Universitas Palangka Raya, 2023)
Policies issued by the Management of Palangka Raya University in 2020, 2021 and 2022 regarding UKT are based on the conditions of the Covid-19 Pandemic. The impact of the Covid-19 Pandemic directly impacted the general economic sector faced by UPR students. This condition requires the leadership to make a policy on the ability of Palangka Raya University students to pay the Single Tuition Fee (UKT) in each semester. The purpose of this research is to formulate a UKT Management strategy during the Covid-19 Pandemic Period at the University of Palangka Raya. This research is a type of qualitative descriptive research conducted in several stages in the descriptive analysis stage with data collection techniques through interviews and questionnaires to key informants through SWOT analysis. SWOT analysis is one of the methods used to complete a decision-making system by considering the criteria and weights of internal and external factors. The results showed that the UKT management strategy during the Covid-19 Pandemic at Palangka Raya University was carried out through a SWOT approach which was influenced by the university's internal and external factors. So based on the results of the QSPM analysis it was found that the priority strategy was to adjust the UKT class changes by taking into account government policies in managing the economy.